The Effect of SP6 Acupressure and Oxytocin Massage on the Duration of the First Stage of Active Labor at the Galala Community Health Center, Tidore Islands - Novita Abdullah; Reny Retnaningsih (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
The active phase of labor is a crucial stage that determines the progress and success of the delivery process. Prolonged labor during this phase can increase the risk of maternal complications and reduce the comfort of the laboring mother. Various non-pharmacological interventions have been developed to support the physiological progress of labor, including acupressure at the SP6 point and oxytocin massage. This study aims to analyze the differences in the effects of SP6 acupressure and oxytocin massage on the duration of the active phase of labor at the Galala Health Center in the Tidore Islands. This study used a quasi-experimental design with a comparative approach in two intervention groups. The sample consisted of 40 mothers in the first stage of active labor who met the inclusion criteria, with 20 respondents in the SP6 acupressure group and 20 respondents in the oxytocin massage group. The duration of the first stage of labor was calculated from 4 cm cervical dilation to complete 10 cm dilation and recorded using a partograph. Data were analyzed univariately to describe the distribution of labor duration and bivariately using the Mann–Whitney U test to assess the difference between the two groups. The results showed that the median duration of the first stage of labor in the SP6 acupressure group was shorter than in the oxytocin massage group. The Mann–Whitney test showed a statistically significant difference between the two intervention groups (p < 0.05). The conclusion of this study indicates that SP6 acupressure is more effective than oxytocin massage in shortening the duration of the first stage of active labor. These findings support the use of SP6 acupressure as a safe and effective nonpharmacological intervention in intrapartum midwifery care in primary health care facilities.